Validation And Evaluation Of A Behaviour Modification Module For Children With Learning Difficulties - Melissa, Chua (2012)
The purpose of this research is to evaluate an existing behaviour modification module for use in the special education classrooms for children with learning disabilities. To achieve the purpose, the objectives of the research are to validate the behaviour modification module that will be used by teachers in special educational classroom to evaluate the teachers’ perception on the potential effectiveness of the module; to evaluate the extent to which teachers are able to apply the strategies in the module; and to evaluate the effectiveness of the strategies in modifying students’ behaviour when applied in a natural setting. A mixed-mode research design was executed to evaluate the behaviour modification module. A survey and single-subject research design was carried out for the quantitative part, and interviews and observations for the qualitative part. Purposive sampling was adopted to select special education teachers for this study. It was also used to identify students with learning disabilities in intact special education classrooms. Data was collected during the teacher training workshop and during implementation in authentic special education classrooms. Two observers were trained for the classroom observation and inter-rater reliability scores were calculated. The quantitative data collected was analysed using descriptive statistics and visual analysis of single subject research data. Qualitative data was analysed using the axial coding method. Triangulation was then executed. Results of the findings showed that the module was valid in terms of content and social validity; teachers who were trained perceived that strategies in the module were potentially effective in changing children’s behaviour; the strategies in the module were effective not only in decreasing off-task and disruptive behaviour but also in increasing desirable behaviour; and teachers were able to apply the strategies frequently and accurately as intended in the module with temporary guidance. Additionally, it was found that for some strategies, the effectiveness is influenced by the teachers’ fidelity in implementing the strategies in the classroom. In summary, the behaviour modification strategies in the module are effective in modifying behaviour.